TOXIC EFFECTS OF POTENTIAL AGENTS FOR BORNEUTRON CAPTURE THERAPY - Makeev , O.; Gubina , O.; Korotkov , A.; Yakovleva , E.; Galliamova, L. (EurasianUnionScientists, 2020)
The aim of the investigation was to study the cytotoxicity of boron-containing compounds intended for boron neutron capture therapy of oncopathology. The studies were performed on human cell cultures. The results obtained indicate a low toxic effect of the GL-57 sample as compared to the GL-63 sample.